Towards the conservation of Sungai Santi catchment: monitoring of land use and vegetation density of mangrove areas - Akmal. S.; Syarina M. S.; S.A. Sharifah Mastura; Mazlan A. Ghaffar (2011)
This paper presents analyses of the land use and land cover change of the Sungai Santi catchment area. The purposes of this study were to delineate mangrove and other land use and land cover and to detect and develop land use masp in catchment aresa over the past 17 years. The NDVI method has been applied to observe the vegetation density of mangrove areas. Landsat TM and SPOT 5 imageries with a combination of ERDAS Imagine 8.4 and Arc View/Arc GIS software were used to detect spatial and temporal changes in land use and vegetation density between the years 1991 and 2007. Sungai Santi catchment experienced multiple changes of land use of varying degrees in 1991 and 2007. Results showed that agricultural land of oil palm and mixed agriculture, water bodies, and forest increased in this area, compared to mangroves and urban areas which decreased by 15.8 % (350 ha) and 23.4 % (223.3 ha) respectively. A land use change matrix indicated that the reduction of mangrove areas was due to an increase in water bodies and forest areas. NDVI method indicated six vegetation density values and the most dominant value was (0.4 – 0.5) which recorded 989.9 ha in 1991 and 981 ha in 2007. Even though the NDVI change matrix depicted a significant transition of 144.1 ha display from (0.4 - 0.5) to (0.5 - 0.6) in 2007, there low vegetation density occurred near the main river. The results showed that on-going land use change and deforestation of mangrove areas can be controlled through strict management of land conversion, and as for the mangrove forest, it has to be through total protection by law. This goal can be achieved by improving the Permanent Forest Reserve law and commitment to adopting a sustainable resource policy